1995
DOI: 10.1111/j.1440-1681.1995.tb02868.x
|View full text |Cite
|
Sign up to set email alerts
|

MAPPING OF ANGIOTENSIN II RECEPTOR SUBTYPES IN PERIPHERAL TISSUES OF SPONTANEOUSLY HYPERTENSIVE RATS BY IN VITRO AUTORADIOGRAPHY

Abstract: 1. The regulation of angiotensin I1 (AII) receptor subtypes was studied in peripheral tissues of 20 week old male spontaneously hypertensive rats (SHR) and age-matched normotensive Wistar-Kyoto (WKY) rats.2. A11 receptor binding was determined by a quantitative in vitro autoradiography using [125I]-[Sar1,Iles]AII as a ligand on the kidney, adrenal gland, thoracic aorta and heart. CV-11974, a specific AT1 receptor antagonist, and CGP42112B, a specific AT2 antagonist, were used in competition with [125I]-[Sarl,I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…The data indicated localization of AT2 throughout the aortic wall (including the medial layer), although the cellular localization of AT2 was not defined. Similar results were obtained in Wistar-Kyoto and spontaneously hypertensive rats (7). Endothelial cells derived from coronary arteries of spontaneously hypertensive rats express AT1 and AT2 in an 80:20 ratio (46).…”
Section: Figuresupporting
confidence: 71%
See 2 more Smart Citations
“…The data indicated localization of AT2 throughout the aortic wall (including the medial layer), although the cellular localization of AT2 was not defined. Similar results were obtained in Wistar-Kyoto and spontaneously hypertensive rats (7). Endothelial cells derived from coronary arteries of spontaneously hypertensive rats express AT1 and AT2 in an 80:20 ratio (46).…”
Section: Figuresupporting
confidence: 71%
“…Because AT2 is present in microvessels at high levels (6)(7)(8), and AT2 activation is increased in atherosclerosis lesions of the aorta (55) and neointima after vascular injury (56), the AT2-mediated depressor effect of the bradykinin/NO system is expected to contribute to the management of BP, coronary microcirculation, and vascular remodeling with AT1 antagonists. We believe we have shown that AT2 stimulation has a novel hemodynamic effect by inhibiting AT1-mediated chronotropic actions without affecting cardiac contractility (24).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that previous reports did not identify AT 2 receptors in the renal vasculature (Song et al, 1994;Song et al, 1995;Haddad and Garcia, 1996;Gao et al, 2003). Indeed, we have been unable to detect AT 2 receptors in freshly isolated preglomerular microvessels from either WKY or SHR using either Western blots or RT-PCR (Gao et al, 2003).…”
Section: Discussioncontrasting
confidence: 56%
“…However, it is realized that the renal expression of AT 1 receptors in SHR has not been consistently shown to be elevated. [45][46][47][48][49][50][51][52] For example, ovariectomy or salt loading in SHR increases renal AT 1 receptors. 44,45 However, renal outer medullary but not cortical AT 1 expression has been reported to be increased in SHR relative to WKY.…”
Section: Discussionmentioning
confidence: 99%